Construction of social indicators using information measuring principles. Case study of real estate prices simulation model - Krylovas, Aleksandras; Kosareva, Natalja; Gudelytė, Laura (Lietuvos matematikos rinkinys, 2011)
The article analyses the data concerning the real estate market of last years in Vilnius. The approach of dichotomous diagnostic operators as general testing tool creation from the empirical data is used and deterministic clusterization of catchments is provided. Based on this analysis, questionnaire concerning the information about catchment is constructed for the evaluation of aggregated appartment price.
Keywords: mathematical modeling; creation of indicators; test; statistical methods